Womandla Health: development and rationale of a behavioral intervention to support HIV treatment adherence among postpartum women in South Africa - Jennifer A. Pellowski; Destry Jensen; Nokwazi Tsawe; Christopher Colvin; Susan Cu-Uvin; Don Operario; Mark Lurie; Abigail Harrison; Landon Myer; Lucia Knight (BMC, 2023)
Abstract Background While Option B + has made great strides in eliminating vertical transmission of HIV and improving access to lifelong antiretroviral therapy (ART) for women, the postpartum period remains a risk period for disengagement from HIV care and non-adherence. Methods Longitudinal qualitative data was collected from 30 women living with HIV in Cape Town, South Africa from pregnancy through 1 year postpartum to examine key barriers and facilitators to HIV treatment adherence across this transition. Participants were also asked about their preferences for behavioral intervention content, format, and scope. The intervention development process was guided by Fernandez et al.'s Intervention Mapping process and was informed by the qualitative data, the wider literature on ART adherence, and Transition Theory. Results The Womandla Health Intervention is a multicomponent intervention consisting of four individual sessions with a lay health worker and four peer group sessions, which span late pregnancy and early postpartum. These sessions are guided by Transition Theory and utilize motivational interviewing techniques to empower women to ascertain their own individual barriers to HIV care and identify solutions and strategies to overcome these barriers. Conclusions This intervention will be tested in a small scale RCT. If successful, findings will provide an innovative approach to HIV treatment by capitalizing on the transition into motherhood to bolster self-care behaviors, focusing on ART adherence and also women's overall postpartum health and psychosocial needs.